2001
DOI: 10.1002/clc.4960240511
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin and mean platelet volume in coronary artery disease

Abstract: SummaryBnckgmund: Large platelets are shown to be hemostatically more active. It has been suggested that mean platelet volume (MPV) is increased during acute myocardial infarction (AMI) and unstable angina pectoris (USAP). However, the underlying mechanism of the phenomenon remains unclear.Hypothesis: In this study, platelets, MPV, and thrombopoietin (TP) levels were investigated in patients with coronary artery disease (CAD) and healthy controls.Methods: Twenty patients with AM1 and 20 patients with USAP were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
112
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 20 publications
12
112
2
6
Order By: Relevance
“…It also stimulates alpha granule secretion from platelets and enhances their ability to aggregate [10]. TPO was positively correlated with MPV in ACS patients in the report of Senaran et al [11].…”
Section: Discussionmentioning
confidence: 83%
“…It also stimulates alpha granule secretion from platelets and enhances their ability to aggregate [10]. TPO was positively correlated with MPV in ACS patients in the report of Senaran et al [11].…”
Section: Discussionmentioning
confidence: 83%
“…Mean platelet volume has been studied in many vascular diseases. Platelets play a pivotal role in atherothrombosis, the major cause of most unstable coronary syndromes and increased MPV levels have been shown as an indicator in myocardial infarcts [4,[11][12][13], congestive heart disease [13], cerebrovascular diseases [14], obesity [15] and hypertensive patients [16,17]. There is a previous study that suggested a relationship between high MPV levels and an increase in the frequency of restenosis in patients who received coronary angioplasty [18].…”
Section: Discussionmentioning
confidence: 99%
“…Large platelets can be defined as stressplatelets. MPV is increased when there is increased destruction of peripheral platelets, and is decreased when there is impairment of platelet production [13]. Since larger platelets are more reactive, MPV is regarded as an indicator of increased cardiovascular disease risk in the general population.…”
Section: Introduction and Aimmentioning
confidence: 99%